Coverage of iron and folic acid supplementation in India: progress under the Anemia Mukt Bharat strategy 2017–20. Issue 5 (28th February 2022) - Joe, William; ,; Patel, Narendra; Alambusha, Ruby; Kulkarni, Bharati; Yadav, Kapil; Sethi, Vani
Abstract: High prevalence of anaemia is a severe public health problem in India. In 2018, India launched the Anemia Mukt Bharat (AMB) strategy that focuses on six beneficiary groups for coverage, six institutional mechanisms for health system strengthening and six programmatic interventions to accelerate reductions in anaemia prevalence. This paper uses the Health Management Information System data (2017–18 to 2019–20) to examine gains in IFA coverage across Indian states. A coverage-based AMB index is computed to review performance across states. After the launch of AMB strategy, the Iron and Folic Acid (IFA) supplementation coverage between 2017–18 and 2019–20 has increased for all beneficiary groups [pregnant women from 78% to 90%; lactating mothers from 34% to 49%; school going adolescent girls (boys) from 23% to 40% (21% to 42%); out-of-school adolescent girls from 6% to 23%; children 5–9 years from 8% to 3% and children 6–59 months from 7% to 15%]. Coverage was relatively low for target groups being served through a multi-departmental convergence mechanism (health and other departments such as education department for schools or women and child development department for Anganwadi centres) than compared to those served by health department alone. However, no major gender disparities are noted in the coverage of IFA supplementation among school-going girls and boys. Bulk of the variations in coverage is attributable to state-specific differences. Training and sensitization workshops for state and district officials are found to be associated with increased coverage across beneficiary groups. The paper argues that despite following international best practices in the field, it is important to harness synergy in programme implementation across line departments to eliminate coverage inefficiencies.